ON THE EARLY STAGES OF THE EVOLUTION OF THE GEOSPHERE AND BIOSPHERE - Dobretsov N.L.; Kolchanov N.A.; Suslov V.V. (My University, 2006)
The conditions necessary for the existence of nucleic-protein life are as follows: the presence of liquid water, an atmosphere, and a magnetic field (all of which protect from meteorites, abrupt changes in temperature, and a flow of charged particles from space) and the availability of nutrients (macro-and microelements in the form of dissolved compounds). In the evolution of the geosphere, complex interference of irreversible processes (general cooling, gravitational differentiation of the Earth's interior, dissipation of hydrogen, etc.) with cyclic processes of varying natures and periodicities (from the endogenic cycles "from Pangea to Pangea" to Milankovitch cycles), these conditions have repeatedly changed; hence, in the coevolution of the geosphere and biosphere, the vector of irreversible evolution was determined by the geosphere. Only with the appearance of the ocean as a global system of homeostasis, which provided the maintenance and leveling of nutrient concentrations in the hydrosphere, and the conveyor of nutrients from the mantle, "the film of life" could begin its expansion from the source of the nutrients. Life itself is a system of homeostasis, but not due to the global size and a vast buffer capacity, but because of the high rate of reactions and presence of a program (genome) that allowed its development (ontogeny) independent from the outside environment. The early stages of the origin and evolution of the biosphere (from the RNA-world to the development of the prokaryotic ecosystems) were characterized by the domination of chemotrophic ecosystems. The geographical ranges of these ecosystems were directly or indirectly (through the atmosphere and hydrosphere) tied to the sources of nutrients in the geosphere, which were in turn connected to various sources of volcanic and geotectonic activity (geothermal waters, "black smokers" along the rift zones, etc.). This gave the biosphere consisting of chemotrophic ecosystems a mosaic appearance composed of separate local oases of life. The decrease of methane and accumulation of O2 in the atmosphere in the geological evolution of the Earth caused the extinction of chemotrophic ecosystems and directed evolution of the biosphere toward autotrophy. Autotrophic photosynthesis gave the biosphere an energy source that was not connected to the geosphere, and for the first time allowed its liberation from the geosphere by developing its own vector of evolution. This vector resulted in the biosphere forming a continuous film of life on the planet by capturing the continents and occupying pelagic and abyssal zones, and the appearance of eukaryotes. The geosphere formed biogeochemical cycles in parallel to the geochemical ones, and comparable in the annual balances of participating matter. © Pleiades Publishing, Inc. 2006.
Keywords: APPEARANCE AND EARLY EVOLUTION OF THE BIOSPHERE; ARCHAEBACTERIA; BIOGEOCHEMICAL CYCLES; PROKARYOTES; RNA-WORLD